Neutrophil-lymphocyte ratio (NLR); an accurate inflammatory marker to predict diabetic foot ulcer amputation: a matched case-control study - Faeze Afshar; Morteza Daraie; Fatemeh Mohammadi; Kiana Seifouri; Samira Amin Afshari; Soheil Heidari Some’eh; Amirhossein Yadegar; Parnian Naghavi; Alireza Esteghamati; Soghra Rabizadeh; Mahsa Abbaszadeh; Manouchehr Nakhjavani; et al. (BMC Endocrine Disorders)
Abstract Background Diabetic foot ulcer (DFU) is a well-known complication of diabetes. The main therapeutic options for treating DFU include surgical debridement. However, conditions such as sensory loss and insufficient blood supply can lead to lower extremity amputations. Inflammatory biomarkers, including the neutrophil‒lymphocyte ratio (NLR) and platelet‒lymphocyte ratio (PLR), have shown promise in predicting the development of diabetes complications. Methods This study included 126 individuals with known DFUs who underwent amputation or debridement surgery during hospitalization between January 2017 and December 2022. The participants were divided into two groups, each containing 63 patients, based on the treatment they received. Analyses were conducted via univariate and multivariate regression models. The linearity of the relationship between each inflammatory index and the risk of amputation was further examined via restricted cubic spline (RCS) curves with four knots. Results Categorical regression analysis showed an elevated risk of amputation in patients with an NLR greater than 6.08, with an OR of 13.090 (95% CI: 5.143–33.320, P < 0.001), compared with those with an NLR less than 6.08. Additionally, patients with a PLR greater than 210 demonstrated a similarly elevated risk of amputation with an OR of 2.31 (95% CI: 1.066‒4.669, P = 0.033); however, those with lymphocyte‒white blood cell ratio (LWR) levels of greater than 0.1265 exhibited reduced likelihood of having amputation (OR: 0.092 (95% CI: 0.038‒0.226, P < 0.001)). Conclusions This study supports that NLR, PLR and LWR may have value as a predictive marker for amputation in patients with DFUs.